(untitled) (Medicine Today, 2021)
Introduction: In Bangladesh, adolescents have unhygienic eating habits; often eating nutritionally unbalanced and junk & fast food diet that is low in dietary fibre and high in cholesterol, simple sugars, fats and additive. These types of dietary habit lead to obesity and dyslipidaemia. Obesity is a worldwide health problem and it is associated with dyslipidaemia and other metabolic syndrome. Objectives: To observe the relationship between Body Mass Index (BMI) and lipid profile among medical college students in Bangladesh. Materials & Methods: This cross sectional observational study was conducted in Department of Medicine, Sir Salimullah Medical College & Mitford Hospital, Dhaka, among the 100 undergraduate medical students. Detailed history, clinical examination and thorough investigations were done and the findings were recorded on a proforma. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Results: Maximum subjects (57.0%) were in the age group 21-23 years. Mean age was 23.42±4.5 years. The prevalence of the different abnormal lipid profile including hypercholesterolaemia, low level of HDL, high level of LDL and hypertriglyceridaemia were: 22.0%, 31.0%, 30.0% and 28.0% respectively. Hypercholesterolaemia and hypertriglyceridaemia levels were significantly associated with increasing body mass index. Conclusion: Overweight and obesity is common among the study subjects and those with higher BMI particularly the older ones tend to have abnormal lipid profile. Therefore adequate dietary control, food habit & life-style modification is needed for prevention of dyslipidemia at early life. Medicine Today 2021 Vol.33(2): 114-119